Acidosis in severe childhood malaria. - English, M; Sauerwein, R; Waruiru, C; Mosobo, M; Obiero, J; Lowe, B; Marsh, K (1997)
Data were prospectively collected on 306 Kenyan children, including blood gases in 258 (75%). Severe malaria caused a predominantly high-anion-gap metabolic acidosis in at least 43% of children. Children with coma and respiratory distress (CM + RD) had greater evidence of renal dysfunction, lower mean pH and higher mean plasma osmolality than those with respiratory distress (RD) or coma (CM) as isolated findings (mean urea 10.7 vs. 6.0 vs. 4.3 mmol/l; mean creatinine 97 vs. 74 vs. 58 mumol/l; mean osmolality 301 vs. 288 vs. 283 mosmol/l; and mean pH 7.16 vs. 7.29 vs. 7.39, respectively, p < 0.001 for each comparison of CM + RD vs. RD or CM). In addition, children with CM + RD had a higher mean blood lactate (6.7 vs. 3.3 mmol/l, p < 0.001), a lower mean haemoglobin (5.5 vs. 7.0 g/dl, p = 0.002) and a lower mean age (26.4 vs. 41.9 months, p < 0.001) than children with CM and accounted for 15/24 (63%) of all deaths. These and previous data implicate hypovolaemia and renal impairment in the pathogenesis of metabolic acidosis in severe childhood malaria. In children who are acidotic, anaemia is strongly associated with lactic acidaemia and may therefore contribute to its pathogenesis. These data also imply that coma in acidotic children (CM + RD) and those with an isolated encephalopathy (CM) may result from quite different pathophysiological mechanisms.